NON PHARMACOLOGICAL TREATMENTS FOR BREAST ENGORGEMENT: A SYSTEMATIC REVIEW - Siregar, Ertitawai; Hardjanti, Triana Sri (Proceedings of the International Conference on Applied Science and Health, 2019)
Background:. Mothers often suffer breast engorgement at the beginning of postpartum, and one of the causes is early breastfeeding cessation. Management of breast engorgement should be done well to support the success of exclusive breastfeeding. This study aimed to review and identify the non- pharmacological treatments that have potential effects on reduced breast engorgementMethods:This was a systematic review prepared according to the standard guidelines of the Joanna Briggs Institute (JBI). Article search used electronically. The two databases used were the PubMed and Cochrane library. English-language articles, and full text using the keywords of "treatment breast engorgement? OR ?lactating? OR ?cabbage compress". The inclusion criteria were the studies with Randomized controlled trial (RCT) published from 2009 to 2019, the respondents were postpartum mothers who breastfed their babies, and intervention was non-pharmacological action research and not a medical action.Results: Out of 5,927 articles resulted from the literature search, there were 5 articles that met the inclusion criteria and included in this systematic review with a total number of 882 participants. The treatment used in dealing with breast engorgement varied, such as 2 studies used cold cabbage leaf and the remaining studies used these non-pharmacological treatments, respectively: hot herbal compresses, cold hollyhock herbal compress, the intervention of Gua sha. All the results of the study stated that the intervention was effective in reducing breast pain and engorgement.Conclusions: Herbal compresses, leaf compresses hollyhock, cabbage compresses and  Gua sha therapy can be used to treat breast engorgement during lactation, but more rigorous follow-up studies are needed to see which interventions are most effective using larger samples.